Boron-doped silicon dioxide, preparation method thereof and low-melting-point borosilicate glass

By doping boron under high temperature and high pressure hydrothermal conditions and preparing homogeneous boron-doped silica particles by sol-gel method, the problems of high firing temperature and volatility of boron components in the existing borosilicate glass are solved, the stability of the material and the homogeneous structure of the glass are achieved, and the convenience of production and the purity of the glass are improved.

CN119528157APending Publication Date: 2025-02-28南通西丽卡新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411777232.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing borosilicate glass has high firing temperature and high equipment requirements. The boron components are easily volatile at high temperatures, affecting the uniformity of the glass, and easily forming borosilicate phase separation.

Method used

Doping boron under high temperature and high pressure hydrothermal conditions to form a hydrothermal stable boron-doped silica framework. Homogeneous boron-doped silica particles were prepared by sol-gel method, and heated to the softening point under high vacuum conditions to prepare borosilicate glass.

Benefits of technology

The stability and thermal expansion coefficient of the material are improved, the volatility of boron and borosilicate phase separation are avoided, and the homogeneous structure is formed, which improves the purity of glass and the convenience of production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses boron-doped silicon dioxide, a preparation method thereof and low-melting-point borosilicate glass, and belongs to the technical field of silica sol. The preparation method of the boron-doped silicon dioxide comprises the following steps: uniformly mixing a boric acid solution, an aluminum sol, a potassium oxalate solution, a sodium carbonate solution and a silica sol, carrying out a hydrothermal reaction in a pressurized state, cooling to obtain homogeneous boron-doped silicon dioxide gel, and finally drying to obtain homogeneous boron-doped silicon dioxide particles. Boron is doped under a high-temperature and high-pressure hydrothermal condition to form a hydrothermal stable boron-doped silicon dioxide skeleton, so that the stability and the thermal expansion coefficient of the material are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technology in the field of silica sol, specifically a boron-doped silica, a preparation method thereof and low-melting-point borosilicate glass. Background Art

[0002] In recent years, with the rapid development of glass coating technology and glass surface deep processing technology, low melting point glass has become more and more popular. As a low melting point glass, borosilicate glass has good optical properties, chemical properties, mechanical properties and thermal stability, and is used in various fields such as chemical industry, aerospace, military, home, hospital, etc.

[0003] At present, borosilicate glass is mainly made by mixing raw materials such as silicon dioxide, borax (or boric acid) and other necessary metal compounds and melting them at about 1600℃. Compared with ordinary glass, its raw materials have a lower melting point and the temperature required for firing to obtain glass is lower, so it is friendly to production. However, it still faces the following problems: 1) The firing temperature is still relatively high, which requires high equipment; 2) The boron component is easy to volatilize at high temperature, affecting the uniformity of the glass; 3) The boron component volatilizes and competes with silicon for alkali metal oxides outside the network framework at high temperature, resulting in borosilicate phase separation.

[0004] In order to solve the above problems in the prior art, the present invention is provided. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a boron-doped silica, a preparation method thereof and a low-melting-point borosilicate glass, which are doped with boron under high-temperature and high-pressure hydrothermal conditions to form a hydrothermally stable boron-doped silica skeleton, thereby enhancing the stability and thermal expansion coefficient of the material.

[0006] The first aspect of the present invention relates to a method for preparing boron-doped silica, comprising uniformly mixing boric acid solution, aluminum sol, potassium oxalate solution, sodium carbonate solution and silica sol, and then subjecting the mixture to a hydrothermal reaction under pressure, followed by cooling to obtain a homogeneous boron-doped silica gel, which is then dried and crushed and sieved to obtain homogeneous boron-doped silica particles.

[0007] For some specific embodiments, the molar ratio of boric acid to silica sol is 1:(3-6); for example, the molar ratio may be 1:3, 1:4, 1:4.5, 1:5, 1:6, etc.

[0008] For some specific embodiments, the molar ratio of aluminum oxide in the aluminum sol to silicon oxide in the silica sol is 1:(50-150); for example, the molar ratio may be 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120, 1:130, 1:140, 1:150, etc.;

[0009] For some specific embodiments, the molar ratio of potassium in potassium oxalate to silicon in silica sol is 1:(5-30); for example, the molar ratio may be 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, etc.;

[0010] For some specific embodiments, the molar ratio of sodium element in sodium carbonate to silicon element in silica sol is 1:(10-45); for example, the molar ratio can be 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, etc.

[0011] Preferably, the mass percentage concentration of the boric acid solution is 6.5% to 8.5%; for example, the mass percentage concentration of the boric acid solution is 6.5%, 6.8%, 7.0%, 7.5%, 8.0%, 8.5%, etc.

[0012] Preferably, the mass solid content of the silica sol is 7% to 16%; for example, the mass solid content of the silica sol may be 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, etc.

[0013] For some specific embodiments, the silica sol is obtained by uniformly mixing a silicon source with an alcohol solvent, an acid catalyst and water in a weight ratio of (50-80): (30-50): 1: (65-100) and then hydrolyzing the mixture; for example, the weight ratio may be 50:30:1:65, 60:30:1:65, 70:30:1:65, 80:30:1:65, 50:40:1:65, 60:40:1:65, 70:4 0:1:65, 80:40:1:65, 50:50:1:65, 60:50:1:65, 70:50:1:65, 80:50:1:65, 50:30:1:85, 60:30:1:85, 70:30:1:85, 80:30:1:85, 50:30:1:100, 60:30:1:100, 70:30:1:100, 80:30:1:100, etc.

[0014] Preferably, the silicon source is at least one of tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane and dimethyldimethoxysilane.

[0015] Preferably, the alcohol solvent is at least one of methanol, ethanol and isopropanol.

[0016] Preferably, the acid catalyst is at least one of acetic acid, citric acid and sulfuric acid.

[0017] Preferably, the water is ultrapure water or deionized water, which has a higher purity and can reduce the introduction of impurities, so that the prepared homogeneous boron-doped silica particles have a higher purity.

[0018] Preferably, ultrasonic stirring is performed at a frequency of 50 to 100 kHz for 0.5 to 1.5 h at 15 to 20° C., the mixture is evenly mixed, and the silica sol is obtained by hydrolysis; for example, ultrasonic stirring can be performed at a frequency of 50 kHz for 0.5 h at 15° C., ultrasonic stirring can be performed at a frequency of 100 kHz for 1.5 h at 20° C., ultrasonic stirring can be performed at a frequency of 85 kHz for 1.0 h at 18° C., etc.

[0019] For some specific implementation schemes, the boric acid solution, aluminum sol, potassium oxalate solution, sodium carbonate solution and silica sol are mechanically stirred together for 3 to 5 minutes to complete the mixing.

[0020] For some specific implementation schemes, the hydrothermal reaction under pressure is: heating to 150-200°C at 0.4-0.9 MPa and keeping warm for 3-6 hours; for example, heating to 150°C and keeping warm for 3 hours at 0.4 MPa, heating to 150°C and keeping warm for 3 hours at 0.6 MPa, heating to 150°C and keeping warm for 3 hours at 0.8 MPa, heating to 170°C and keeping warm for 3 hours at 0.4 MPa, heating to 170℃ and keep warm for 3h, heat to 170℃ at 0.9MPa and keep warm for 3h, heat to 200℃ at 0.4MPa and keep warm for 3h, heat to 200℃ at 0.5MPa and keep warm for 3h, heat to 200℃ at 0.9MPa and keep warm for 3h, heat to 200℃ at 0.4MPa and keep warm for 6h, heat to 200℃ at 0.5MPa and keep warm for 6h, heat to 200℃ at 0.9MPa and keep warm for 6h, etc.

[0021] For some specific embodiments, the cooling is natural cooling, and the cooling rate is 1 to 10°C / min; for example, the cooling rate can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc.

[0022] For some specific implementation schemes, the drying treatment is at 80-120°C and kept warm for 2-3 hours; for example, it can be kept warm at 80°C for 2 hours, 90°C for 2 hours, 100°C for 2 hours, 110°C for 2 hours, 120°C for 2 hours, 80°C for 3 hours, 90°C for 3 hours, 100°C for 3 hours, 110°C for 3 hours, 120°C for 3 hours, etc.

[0023] The second aspect of the present invention relates to a homogeneous boron-doped silica particle, which is prepared by the above method and has Si-OB bonds as the skeleton.

[0024] Depending on the application scenario, the boron-doped silica can be crushed using different crushing process systems, such as primary crushing or multi-stage crushing, to obtain the required particle size; preferably, the average particle size of the boron-doped silica particles is 75 to 150 μm.

[0025] The third aspect of the present invention relates to a low melting point borosilicate glass, which is -3 ~10 -5 Under Pa conditions, the homogeneous boron-doped silica particles are heated to 1000-1200° C. for melting, kept warm for 1.5-2 hours, and finally cooled naturally to obtain the product.

[0026] For example, a high vacuum can be 10 -3 Pa, 10 -4 Pa, 10 -5 Pa et al.

[0027] For example, the melt insulation can be 1000°C for 1.5h, 1100°C for 1.5h, 1200°C for 1.5h, 1000°C for 2h, 1100°C for 2h, 1200°C for 2h, etc.

[0028] For example, the temperature is increased to 1000-1200° C. at a rate of 2-5° C. / min; for example, the temperature increase rate may be 2° C. / min, 3° C. / min, 4° C. / min, 5° C. / min, etc.

[0029] Compared with the prior art, the present invention has the following technical effects:

[0030] 1) Boron-doped silica is prepared by sol-gel method under pressurized hydrothermal conditions. In this process, silica sol is fully hydrolyzed and polymerized under acidic conditions, and boron ions fill the gaps to form a stable Si-OB skeleton, thereby ensuring that the boron-doped silica can remain stable in the molten state, avoiding boron volatilization and boron-silicon phase separation, and forming a homogeneous structure.

[0031] 2) Boron-doped silica produced by the sol-gel method has no side reaction products, and the impurities are only related to the original impurities in the raw materials, so the purity is relatively high, not less than 99.99%;

[0032] 3) The preparation method is simple and the process flow is easy to operate;

[0033] 4) For the production of borosilicate glass, potassium and sodium act as fluxes at high temperatures to lower the softening point of high-temperature glass. Boric acid, as a sintering binder for silica, is dehydrated and converted into boron oxide during sintering. Boron oxide acts as a binder at high temperatures, which can lower the sintering temperature of silica, thereby lowering the softening point of borosilicate glass. In addition, during the high-temperature sintering process, silica will react with boron oxide to form tridymite and cristobalite. These newly formed compounds have lower melting points and softening points, and boron doping can also reduce the viscosity of silica at high temperatures, making it easier to flow at high temperatures, thereby lowering the softening point. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with specific embodiments. Experimental methods without specific conditions in the examples are carried out according to conventional methods and conditions.

[0035] Example 1

[0036] The process of preparing borosilicate glass in this embodiment is as follows.

[0037] Take 55 g of tetramethoxysilane, 34 g of methanol, 1 g of acetic acid and 76 g of ultrapure water, mix and stir evenly; at 15°C, treat the above solution by ultrasonic treatment for 1 hour to obtain silica sol with a solid content of 15%;

[0038] Take boron oxide powder and prepare 8% by mass boric acid solution at 85°C; mix the above silica sol with 60.5g of boric acid solution, 3g of 20% by mass aluminum sol (as aluminum source, Suzhou Routao New Materials Co., Ltd., RT-01061), 6g of 30% by mass potassium oxalate solution, and 5g of 25% by mass sodium carbonate solution, and stir for 3 minutes; then place it in a hydrothermal reactor, react at 150°C, keep warm for 5 hours, and naturally cool to room temperature to obtain a homogeneous boron-doped silica gel; then dry it at 100°C, and after drying, crush and sieve to obtain boron-doped silica particles with an average particle size of 150μm.

[0039] The boron-doped silica particles were placed in a high vacuum for 10 -3 Under the condition of 1.37 Pa, the temperature was raised to 1200°C at a rate of 5°C / min, kept at that temperature for 2 hours, and finally cooled naturally to obtain a glassy substance. The glassy substance was obtained by firing at a relatively low temperature, namely borosilicate glass.

[0040] Example 2

[0041] Take 65 g of tetraethoxysilane, 30 g of ethanol, 1 g of acetic acid and 90 g of ultrapure water, mix and stir evenly; at 18°C, ultrasonically treat the above solution for 1 hour to obtain a silica sol with a solid content of 12%;

[0042] Take boron oxide powder and prepare a boric acid solution with a mass fraction of 8.5% at 90°C; mix the above silica sol with 73.4g of boric acid solution, 5g of aluminum sol with a mass fraction of 23%, 4g of potassium oxalate solution with a mass fraction of 35%, and 2g of sodium carbonate solution with a mass fraction of 28%, and stir for 5 minutes; then place it in a hydrothermal reactor, react at 200°C, keep it warm for 3 hours, and naturally cool to room temperature to obtain a homogeneous boron-doped silica gel; then dry it at 100°C, and after drying, crush and sieve to obtain boron-doped silica particles with an average particle size of 80μm.

[0043] The boron-doped silica particles were placed in a high vacuum for 10 -3 Pa conditions, the temperature was raised to 1000°C at a rate of 2°C / min, kept for 2 h, and then naturally cooled to obtain borosilicate glass.

[0044] Example 3

[0045] Take 80 g of tetramethoxysilane, 50 g of isopropanol, 1 g of citric acid and 100 g of ultrapure water, mix and stir evenly; at 16°C, treat the above solution by ultrasonic treatment for 1 hour to obtain a silica sol with a solid content of 16%;

[0046] Take boron oxide powder and prepare a 7% by mass boric acid solution at 84°C; mix the above silica sol with 114g of boric acid solution, 8g of 20% by mass aluminum sol, 10g of 28% by mass potassium oxalate solution, and 3g of 25% by mass sodium carbonate solution, and stir for 5 minutes; then place it in a hydrothermal reactor, react at 180°C, keep it warm for 4 hours, and naturally cool to room temperature to obtain a homogeneous boron-doped silica gel; then dry it at 100°C, and after drying, crush and sieve to obtain boron-doped silica particles with an average particle size of 100 μm.

[0047] The boron-doped silica particles were placed in a high vacuum for 10 -4 Under Pa conditions, the temperature was raised to 1150°C at a rate of 3°C / min, kept for 2 h, and then naturally cooled to obtain borosilicate glass.

[0048] Example 4

[0049] Take 60g of methyltrimethoxysilane, 40g of methanol, 1g of acetic acid and 82g of ultrapure water, mix and stir evenly; at 20°C, ultrasonically treat the above solution for 1h to obtain silica sol with a solid content of 15%;

[0050] Take boron oxide powder and prepare a 7.5% by mass boric acid solution at 84°C; mix the above silica sol with 96g of boric acid solution, 6g of 26% by mass aluminum sol, 5g of 30% by mass potassium oxalate solution, and 8g of 25% by mass sodium carbonate solution, and stir for 4 minutes; then place it in a hydrothermal reactor, react at 180°C, keep it warm for 5 hours, and naturally cool to room temperature to obtain a homogeneous boron-doped silica gel; then dry it at 100°C, and after drying, crush and sieve to obtain boron-doped silica particles with an average particle size of 130μm.

[0051] The boron-doped silica particles were placed in a high vacuum for 10 -3 Pa conditions, the temperature was raised to 1000°C at a rate of 4°C / min, kept for 2 h, and then naturally cooled to obtain borosilicate glass.

[0052] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing boron-doped silicon dioxide, characterized in that: The boric acid solution, aluminum sol, potassium oxalate solution, sodium carbonate solution and silica sol are mixed evenly, and then subjected to hydrothermal reaction under pressure, and then cooled to obtain a homogeneous boron-doped silica gel, which is dried, crushed and sieved to obtain homogeneous boron-doped silica particles.

2. The method for preparing boron-doped silicon dioxide according to claim 1, characterized in that: The molar ratio of aluminum oxide in aluminum sol to silicon dioxide in silica sol is 1: (50-150), the molar ratio of potassium element in potassium oxalate to silicon element in silica sol is 1: (5-30), the molar ratio of sodium element in sodium carbonate to silicon element in silica sol is 1: (10-45), and the molar ratio of boric acid to silicon dioxide is 1: (3-6); preferably, the mass solid content of silica sol is 7%-16%, and the mass percentage concentration of boric acid solution is 6.5%-8.5%.

3. The method for preparing boron-doped silicon dioxide according to claim 1 or 2, characterized in that: The silica sol is obtained by uniformly mixing a silicon source with an alcohol solvent, an acid catalyst and water in a weight ratio of (50-80): (30-50): 1: (65-100) and then hydrolyzing the mixture.

4. The method for preparing boron-doped silicon dioxide according to claim 3, characterized in that: The silicon source is at least one of tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane and dimethyldimethoxysilane; preferably, the alcohol solvent is at least one of methanol, ethanol and isopropanol; preferably, the acid catalyst is at least one of acetic acid, citric acid and sulfuric acid.

5. The method for preparing boron-doped silicon dioxide according to claim 3, characterized in that: The mixture is ultrasonically stirred at a frequency of 50 to 100 kHz for 0.5 to 1.5 hours at 15 to 20° C. to mix evenly and hydrolyze to obtain silica sol.

6. The method for preparing boron-doped silicon dioxide according to claim 1, characterized in that: The boric acid solution, aluminum sol, potassium oxalate solution, sodium carbonate solution and silica sol are mechanically stirred together for 3 to 5 minutes to complete mixing; preferably, the hydrothermal reaction under pressure is 0.4 to 0.9 MPa, heated to 150 to 200° C., and kept warm for 3 to 6 hours; preferably, cooling is natural cooling, and the cooling rate is 1 to 10° C. / min; preferably, the drying treatment is 80 to 120° C., and kept warm for 2 to 3 hours.

7. A homogeneous boron-doped silica particle, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6, and has Si-OB bond as the skeleton.

8. The homogeneous boron-doped silica particles according to claim 7, characterized in that: The average particle size of the homogeneous boron-doped silica particles is 75 to 150 μm.

9. A low melting point borosilicate glass, characterized in that: In high vacuum 10 -3 ~10 -5 Under Pa conditions, homogeneous boron-doped silica particles are heated to 1000-1200° C., kept warm for 1.5-2 hours in a molten state, and finally cooled naturally to obtain the obtained product.

10. The low melting point borosilicate glass according to claim 9, characterized in that: The temperature is raised to 1000-1200°C at a rate of 2-5°C / min.